Percentage amplitude of fluctuation and structural covariance changes of subjective cognitive decline in patients: A multimodal imaging study - Xu, Ke; Wei, Yichen; Zhang, Shuming; Zhao, Lihua; Geng, Bowen; Mai, Wei; Li, Pengyu; Liang, Lingyan; Chen, Duoli; Zeng, Xiao; Deng, Demao; Liu, Peng (Frontiers in Neuroscience, 2022)
Background: Subjective cognitive decline (SCD) may be the first clinical sign of Alzheimer’s disease (AD). It is still not well known about the possible neural mechanisms of SCD. This study aimed to compare percent amplitude of fluctuation (PerAF) and structural covariance patterns in SCD patients and healthy controls (HCs). Methods: We enrolled 53 SCD patients and 65 HCs. Resting-state functional magnetic resonance imaging (MRI) data and T1-weighted anatomical brain 3.0-T MRI scans were collected. The PerAF approach was applied to distinguish altered brain functions between the two groups. A whole-brain voxel-based morphometry analysis was performed, and all significant regions were selected as regions of interest (ROIs) for the structural covariance analysis. Statistical analysis was performed using two-sample t-tests, and multiple regressions were applied to examine the relationships between neuroimaging findings and clinical symptoms. Results: Functional MRI results revealed significantly increased PerAF including right hippocampus (HIPP) and right thalamus (THA) in SCD patients relative to HCs. Gray matter volume (GMV) results demonstrated decreased GMV in the bilateral ventrolateral prefrontal cortex (vlPFC) and right insula in SCD patients relative to HCs. Taking these three areas including the bilateral vlPFC and right insula as regions of interest (ROIs), differences were observed in the structural covariance of the ROIs with several regions between the two groups. Additionally, significant correlations were observed between neuroimaging findings and clinical symptoms. Conclusions: Our study investigated the abnormal PerAF and structural covariance patterns in SCD patients, which might provide new insights into the pathological mechanisms of SCD.